Sustainable formation of tricarballylic acid from citric acid over highly stable Pd/Nb2O5·nH2O catalysts - Stuyck, Wouter; Bugaev, Aram L.; Nelis, Tom; de Oliveira-Silva, Rodrigo; Smolders, Simon; Usoltsev, Oleg A.; Arenas Esteban, Daniel; Bals, Sara; Sakellariou, Dimitrios; De Vos, Dirk (Journal of catalysis, 2022)
[Display omitted] •Nb2O5·nH2O proved to be a stable and efficient catalyst for the dehydration of citric acid at mild reaction temperatures.•Investigation of the interaction of citric acid with the Nb2O5·nH2O surface by 13C MAS NMR.•Synthesis of bifunctional Pd/Nb2O5·nH2O via a low-temperature reduction method to preserve the acid properties of the support.•Yields of tricarballylic acid exceeding 90% over multiple runs. Recently, a reaction sequence was developed for the production of tricarballylic acid, an interesting plasticiser precursor, from citric acid by using a H-Beta zeolite and Pd/C catalyst. Although yields of 85% of tricarballylic acid were obtained, citric acid elicited Al leaching from the zeolite framework, resulting in loss of activity. In this work, Nb2O5·nH2O was found to be a stable and performant catalyst for this reaction, and a strong involvement of the hydroxyl group of citric acid with the Nb2O5·nH2O surface was observed by 13C MAS NMR. Next, Pd/Nb2O5·nH2O catalysts were synthesized via a low temperature reduction method to preserve the acidity of the Nb2O5·nH2O support; the nature of the Pd phase was examined by XAS. In presence of a 0.6 wt% Pd/Nb2O5·nH2O catalyst, yields over 90% of tricarballylic acid were obtained over multiple runs. Finally, this catalyst was also suitable for the dehydration-hydrogenation of other monohydroxy carboxylic acids.